Macroscopically uniform interface layer with Li+ conductive channels for high-performance Li metal batteries - Qian Chen; Binyin Gao; Zhilin Yang; Yong Li; QingWei Zhai; Yangyu Jia; Qiannan Zhang; Xiaokang Gu; Jinghan Zuo; Lei Wang; Tianshuai Wang; Pengbo Zhai; et al. (Nature Communications)
Abstract The numerous grainboundaries solid electrolyte interface, whether naturally occurring or artificially designed, leads to non-uniform Li metal deposition and consequently results in poor full-battery performance. Herein, a lithium-ion selective transport layer is reported to achieve a highly efficient and dendrite-free lithium metal anode. The layer-by-layer assembled protonated carbon nitride nanosheets present uniform macroscopical structure without grainboundaries. The carbon nitride with ordered pores in basal plane provides high-speed lithium-ion transport channels with low tortuosity. Consequently, the assembled 324 Wh kg−1 pouch cell exhibits 300 stable cycles with a capacity retention of 90.0% and an average Coulombic efficiency up to 99.7%. The ultra-dense Li metal anode makes current collector-free anode possible, achieving high energy density and long cycle life of a 7 Ah cell (506 Wh kg−1, 160 cycles). Thus, it is proved that a macroscopically uniform interface layer with lithium-ion conductive channels could achieve Li metal battery with promising application potential.